Dataset for article entitled "The Programme Director and the Teaching Excellence Framework: How do we train the former to survive the latter?" - Massie, Ruth (Cranfield University, 2018)
This is the base data from the survey undertaken for "The Programme Director and the Teaching Excellence Framework: How do we train the former to survive the latter?" in Higher Education Quarterly. (The questionnaire used is at https://doi.org/10.17862/cranfield.rd.6652817.)
Keywords: 'Programme Director'; 'Teaching Excellence Framework'; 'Higher Education'; 'Organisational Behaviour'; 'Business and Management not elsewhere classified'